Tourism Marketing Management Strategy At The Department Of Tourism And Culture Of Trenggalek Regency - Gaung Perwira Yustika; Muchlis, Muhammad Arfan (Apik Cahaya Ilmu, 2023)
Industry competition in Indonesia is currently very tight, especially in the world of tourism, where each region competes to highlight its uniqueness. With this very tight competition, the Tourism and Culture Office of Trenggalek Regency has developed a strategy for marketing management to promote tourism potential in the region. The aim of the tourism marketing management strategy is to increase the existing tourism potential in the area. This research method is descriptive and qualitative. The informants in this study were the Head of the Tourism Marketing Division, and the Head of the Tourism Promotion and Information Section. Data collection was carried out through direct observation, interviews and documentation. Data collection took place in the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this study conclude that the implementation of the tourism marketing strategy is good, although still not optimal, tourism development is supported by official programs in the form of tourism promotion measures using advertising media or tools such as print media, electronic media and exhibitions.